Description of gingival status in children aged 10-12 years at SDN 01 Jajawar, Banjar City: Gambaran status gingiva pada anak usia 10-12 tahun di SDN 01 Jajawar Kota Banjar - Reinhart, Ignatius Adriel; Abigayl, Ivana; Alfiyola, Elsa; Ginazdi, Natasya Humaira; Milenia, Irena; Yuliadewi, Dicha; Sihombing, Juwita Sulastry (Makassar Dental Journal, 2024)
In Indonesia, gingivitis ranks second, reaching 96.58%. The 2018 Riskesdas data shows gingivitis cases at 74.1%. Gingivitis is an inflammation of the gingiva caused by dental plaque. Gingivitis can also be influenced by hormonal factors. This study was con-ducted to determine the gingival status of children aged 10-12 years at SDN 01 Jajawar Banjar City. Descriptive study with cross sectional design, using total sampling technique on grade V and grade VI students totalling 58 students. Assessment of gingivitis was assessed using the modified gingival index. The results showed that 1 student had no gingivitis (1.7%), 20 students had the mild (34.5%), 33 students had the moderate (56.9%), and 4 students had the severe (6.9%). It is concluded that the highest pre-valence of gingivitis was at the age of 11 years at 50%. The prevalence of gingivitis in girls (58.6%) was higher than boys (38.7%).